Analysis of volatile organic compounds in Korean-bred strawberries: insights for improving fruit flavor - Jee, Eungu; Do, Eunsu; Gil, Chan Saem; Kim, Seolah; Lee, Sun Yi; Lee, Seonghee; Ku, Kang-Mo (Frontiers in Plant Science, 2024)
The strawberry industry has been advanced to 65% growth in South Korea over the past decade, leading in fruit and vegetable production value. With sweetness and acidity, volatile organic compounds (VOCs) are also important factors to determine favorable flavor in strawberries. The composition of VOCs varies depending on strawberry cultivars; however, research has been mostly conducted to focus on specific commercial cultivars. Therefore, this study was conducted to develop the VOC database of various strawberry cultivars from domestic and foreign resources. 61 different strawberry cultivars from Korea (45), the USA (7), Japan (8), and France (1) were analyzed for their VOC contents. The analysis was conducted using Tenax TA Thermo Desorption tubes (TD tubes) and Gas Chromatography-Mass Spectrometry (GC-MS). Through the chemical analyses, it was revealed that a total of 122 compounds were categorized to esters, alcohols, terpenes, and lactones. Among them, esters were found to account for the highest proportion, exhibiting 46.5% of total VOCs in Korean cultivars. Among the cultivars tested, ‘Arihyang’, ‘Sunnyberry’ and ‘Kingsberry’ exhibited the highest variation of VOCs (97 types) detected, while ‘Seolhong’ had the highest concentration overall (57.5μg·kg-1 FW). In comparison to USA cultivars abundant in γ-decalactone (peach-like fruity aroma), most domestic cultivars were notably deficient in this fruity aroma compound. Among the cultivars assessed, ‘Misohyang’ showed a high content of γ-decalactone, suggesting the potential breeding germplasm to enhance the flavor in Korean strawberries. Additionally, through the comparative analysis of VOCs among different breeding germplasm, it is possible to identify important VOCs for the development of new cultivars with improved fruit flavor.